2001
DOI: 10.1097/00002030-200111230-00002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV effects of chloroquine: mechanisms of inhibition and spectrum of activity

Abstract: At clinically achievable concentrations chloroquine inhibits HIV-1 post-integrationally by affecting newly produced viral envelope glycoproteins, and the drug has broad-spectrum anti-HIV-1 and HIV-2 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
110
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 27 publications
10
110
3
Order By: Relevance
“…CQ is relatively inexpensive, is widely available, and has been shown to inhibit HIV-1 replication by disrupting the formation of glycoproteins in the viral envelope resulting in a broad spectrum of antiviral activity (Tsai et al, 1990;Savarino et al, 2001a). In keeping with previous reports (Savarino et al, 2001a), we found that CQ exhibited anti-HIV activity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…CQ is relatively inexpensive, is widely available, and has been shown to inhibit HIV-1 replication by disrupting the formation of glycoproteins in the viral envelope resulting in a broad spectrum of antiviral activity (Tsai et al, 1990;Savarino et al, 2001a). In keeping with previous reports (Savarino et al, 2001a), we found that CQ exhibited anti-HIV activity.…”
Section: Discussionsupporting
confidence: 89%
“…CQ suppresses HIV-1 and -2 replication in vitro (Tsai et al, 1990;Savarino et al, 2001a) (as does its analog hydroxyCQ; Sperber et al, 1997;Boelaert et al, 2001), possibly by inhibition of HIV gp120 (Tsai et al, 1990). In vitro studies examining CQ in HIV-infected cells has shown some additivity with zidovudine (Boelaert et al, 2001) and synergy with numerous protease inhibitors (PIs) in T cell lines (Savarino et al, 2004).…”
mentioning
confidence: 99%
“…Until the emergence of drug-resistant parasites, these drugs were the most effective means to treat malaria, a disease that claims 1 to 3 million lives annually (Foley and Tilley, 1998). In addition to malaria, quinoline-containing and structurally related compounds have been used in the treatment of lupus erythematosus (Van Beek and Piette, 2001), arthritis (Fox, 1993), and HIV (Savarino et al, 2001) and have been shown to exhibit antiprion activity (Korth et al, 2001). Remarkably, there is no clear mechanism known for the therapeutic action of these drugs in any of these diseases.…”
mentioning
confidence: 99%
“…In vitro inhibition of HIV-1 replication in cultured peripheral blood lymphocytes has been observed only at CQ concentrations from 3 to 10 M (8, 10). This inhibition is associated with alterations in gp120 glycosylation (10). Nevertheless, such high CQ concentrations are toxic to peripheral blood lymphocytes (8) (data not shown).…”
mentioning
confidence: 99%